ANALISIS PENGARUH FREE CASH FLOW, GROWTH, MARKET TO BOOK VALUE, PROFITABILITY, DAN LEVERAGE TERHADAP DIVIDEND PAYOUT RATIO (Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Rizqi Pramanda, Fauzian; Indriani, Astiwi (Diponegoro Journal of Management, 2021)
The purpose of this study was to analyse and investigate the relationship of Free Cash Flow, Growth, Market to Book Value, Profitability, Leverage to Dividend Payout Ratio. Study conducted in manufacturing industries which has listed in Indonesian Stock Exchange from 2016 until 2018. Population used in this research is manufacturing industries which has listed in Indonesian Stock Exchange from 2016 until 2018. The sampling method that been used in this study is purposive sampling, and acquired result 51 samples of manufacturing companies that been tested. Method that been used in this study is multiple linear regression. The result of this study shows Market to Book Value dan Return on Assets variables has significantly positive relationship to Dividend Payout Ratio. Growth Sales has significantly negative relationship to Dividend Payout Ratio. Free Cash Flow and Debt to Equity Ratio variables has positive relationship but insignificant to Dividend Payout Ratio.